General surgery under limited conditions on the Syrian border - Mustafa Senturk (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Aim: People living in the countryside are less to have access to health care than those Living in the city center. In addition to this, when migrants are added, it becomes more diffi cult to use health services. Although 20% of the US population lives in rural areas, only 9% of physicians work in these areas, and general surgeons seem to be inadequate in small rural towns. This study was planned to determine the general surgical procedures performed in the district state hospital. Methods: The study was carried out in the Ceylanpinar State Hospital with 50 beds, located approximately 150 km far from the city center of Sanliurfa. İn 2018, patient fi les were reviewed for general surgery polyclinic. Elective and urgent procedures were recorded and their results were evaluated. Patients who were operated for trauma were not included in the study